Fundamental Relation on HvBE-Algebras - Iranmanesh, Farzad; Ghadiri, Mansour; Borumand Saeid, Arsham (Bulletin of the Section of Logic, 2023)
In this paper, we are going to introduce a fundamental relation on \(H_vBE\)-algebra and investigate some of properties, also construct new \((H_v)BE\)-algebras via this relation. We show that quotient of any \(H_vBE\)-algebra via a regular regulation is an \(H_vBE\)-algebra and this quotient, via any strongly relation is a \(BE\)-algebra. Furthermore, we investigate that under what conditions some relations on \(H_vBE\)-algebra are transitive relations.